Clearing and settlement systems and the role of regulation - Milne, Alistair (Henry Stewart Talks, 2010)
The different post-trade processes that occur after the execution of a securities trade, Key participants in clearing and settlement of the broker, custodian, central counterparty, commercial bank, and central security depository, The risks in clearing and settlement, from the perspective both of the broker conducting the trade and for the system as a whole, The different arrangements used to control these risks, Is there effective competition in clearing and settlement